82‐2: Substrate‐Free Flexible Electronics Manufacturing by Weak Bonding Method. Issue 1 (30th May 2018) - Ke, Tsung-Ying; Lee, Chih-Tsung; Cheng, Kuei-Ning; Su, Wei-Jen; Kang, Ting; Wang, Wan-Tsang; Liu, Chun-Hsin; Lin, Yu-Hsin
Abstract : By using weak bonding method, a flexible electronics either of organic or inorganic substrate formed on a rigid carrier glass can be directly separated from the carrier glass, with protection film‐assisted, by mechanical de‐bonding method. Without PI substrate, multi‐advantages are demonstrated for flexible OLED display production.